Two-dimensional tantalum disulfide: controlling structure and properties via synthesis. (2nd January 2018) - Zhao, Rui; Grisafe, Benjamin; Ghosh, Ram Krishna; Holoviak, Stephen; Wang, Baoming; Wang, Ke; Briggs, Natalie; Haque, Aman; Datta, Suman; Robinson, Joshua
Abstract: Tantalum disulfide (TaS2 ) is a transition metal dichalcogenide (TMD) that exhibits phase transition induced electronic property modulation at low temperature. However, the appropriate phase must be grown to enable the semiconductor/metal transition that is of interest for next generation electronic applications. In this work, we demonstrate direct and controllable synthesis of ultra-thin 1T-TaS2 and 2H-TaS2 on a variety of substrates (sapphire, SiO2 /Si, and graphene) via powder vapor deposition. The synthesis process leads to single crystal domains ranging from 20 to 200 nm thick and 1–10 µ m on a side. The TaS2 phase (1T or 2H) is controlled by synthesis temperature, which subsequently is shown to control the electronic properties. Furthermore, this work constitutes the first demonstration of a metal–insulator phase transition in directly synthesized 1T-TaS2 films and domains by electronic means.